Design of Geothermal District Heating System of Universiade 2005 Athletes' Village - Ünerdem, Yiğit; Toksoy, Macit (Izmir Institute of Technology, 2005)
Geothermal energy, which is the Earth.s interior energy, has a broad application area for heating and energy production purposes. To develop healthy geothermal energy projects, conceptual planning study is one of the important tasks which should be done initially. Conceptual planning studies consists of technical, economical and political evaluation of the project showing that whether the project is feasible or not. In this study, conceptual planning study is applied to the Athletes. Village which has a dwelling area of 97,446 m2. The total peak demand including hot water need for this system design is 11,7 MWt. The existing heating system is fuel-firing system. A comparison between the existing system with geothermal district heating system is done by this study. The hot water at 140 C, which is planned to be extracted from new drilled wells, is first cooled down to 120 C and afterwards designed to give its energy to the closed city loop. Finally, city loop water will circulate in the buildings within the temperature range of 85 C/55 C. The economy of the system is studied for two different well locations considering different participating costs and operating costs.The monthly fixed charges which make the internal rate of return positive around 0 % is determined for the investor for different participating costs varying between $ 1250 and $ 2500. At the end, the net present worths for the payments that would be done to the heating systems are calculated for the consumers. As a result of the economic feasibility study, it is determined that geothermal district heating design would be feasible for the consumers when the same comfort conditions are considered for both of the designs.
Thesis (Master)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2005
Includes bibliographical references (leaves: 70-72)
Text in English; Abstract: Turkish and English
xi, 75 leaves
Keywords: TH7416.5 .U56 2005; Geothermal district heating--Izmir (Turkey)